Maximizing VA Remote Patient Monitoring During the COVID-19 Response - Buck, Catherine; Kobb, Rita; Sandreth, Ron; Alexander, Lisa; Olliff, Sherron; Anderson, Carla; Westfall, Carol; Graaff, Laurie; Giovannucci, Joseph; Rollins, Aszur (Telehealth and Medicine Today, 2021)
Abstract Objective: The Veterans Health Administration has one of the largest remote patient monitoring programs in the United States and is supported by an enterprise-wide infrastructure for providers, clinicians, staff, Veterans, and caregivers. The COVID-19 pandemic, however, presented new challenges: a sudden need to provide large-scale remote monitoring for a new disease that did not yet have a disease management protocol. VHA needed to be ready within weeks to provide this daily monitoring for hundreds — even thousands — of Veterans. Methods: The U.S. Department of Veterans Affairs Office of Connected Care already had a comprehensive infrastructure in place for its Remote Patient Monitoring – Home Telehealth (RPM – HT) program. Connected Care activated and built on this infrastructure to support providers, clinicians, and staff in their efforts to rapidly bring RPM – HT to Veterans across the nation when they had COVID-19 symptoms or exposure. To do this, Connected Care activated an emergency management plan, rapidly developed a new COVID-19-specific disease management protocol, added weekend monitoring, and procured critically needed monitoring supplies, such as thermometers and pulse oximeters. Connected Care’s strong foundation allowed for innovation and flexibility, such as the training of non-RPM – HT staff in RPM – HT processes, RPM – HT enrollment within acute care settings, and new strategic partnerships. Outcomes: More than 23,500 Veterans were enrolled for COVID-19-related monitoring from March 2020 to May 2021. At points in December 2020 and January 2021, the number of Veterans being monitored in a single day topped 2,000. Even with this rapid buildup, patient satisfaction levels remained at about 90% in numerous categories. In addition, the percentage of Veterans admitted to VA facilities while on COVID-19-related home monitoring has been extremely low, at 4%, a potential indicator that the monitoring system has been helpful in enabling Veterans who did have the virus to convalesce at home. Further study is needed to determine the impact RPM – HT enrollment for COVID-19 care had on the need for inpatient care. Conclusion: The Office of Connected Care’s established, enterprise-wide RPM – HT business, clinical, and technical infrastructure enabled VHA to enter the COVID-19 public health emergency well-positioned for the rapid deployment and growth of at-home and mobile monitoring. As the COVID-19 emergency made at-home management of Veterans increasingly important, the national RPM – HT program successfully adapted its practices to meet Veteran, caregiver, and staff needs.